Effect of dexmedetomidine as an adjuvant to levobupivacaine in supraclavicular brachial plexus block: A randomized double-blind prospective study - Haramritpal Kaur; Gurpreet Singh; Sunita Rani; Kewal Krishan Gupta; Mukesh Kumar; Amanjot Singh Rajpal; Shobha Aggarwal (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: Regional anesthesia is a recommended technique for upper and lower limb surgeries with better postoperative profile. In this, randomized, double-blind study, we evaluated the effectiveness of the addition of dexmedetomidine to varying concentration of levobupivacaine for supra clavicular brachial plexus block. Material and Methods: After obtaining ethical Committee approval, a double-blind, randomized prospective clinical study was conducted on 90 American Society of Anesthesiologist Grade I and II patients in the age group of 18-55 years, divided randomly into two groups: Group A received 40 ml of solution containing 30 ml 0.5% levobupivacaine and 10 ml 1% lignocaine and group B received 40 ml of solution containing 30 ml 0.25% levobupivacaine and 10 ml 1% lignocaine with dexmedetomidine 1 microg/kg for supraclavicular brachial plexus block. Besides effectiveness, other parameters observed were: duration of sensory blockade; onset and duration of motor blockade; duration of postoperative analgesia; and patient satisfaction score. Results: Onset of sensory and motor blockade was 7.6 ± 1.006 min and 8.3 ± 0.877 min in group A, while it was 6.96 ± 1.077 min an 7.6 ± 1.1 min in group B, respectively. The difference was statistically significant (P < 0.05). Duration of sensory block was 8.5 ± 0.77 h in group A and 8.5 ± 0.98 in group B (P > 0.05). Duration of motor block was 8.45 ± 0.75 h in group A and 5.6 ± 0.98 in group B (P < 0.05). Duration of analgesia was 8.5 ± 0.77 h in group A and 9.2 ± 1.05 in group B (P < 0.05). Conclusion: Addition of 1 microg/kg dexmedetomidine to 0.25% levobupivacaine for supraclaviclar plexus block shortens sensory, motor block onset time and motor block durations, extends sensory block, and analgesia durations. Reduction in total levobupivacaine dose also increases the safety margin of the block.